Electromagnetic-acoustic biphysical cloak designed through topology optimization - Fujii, Garuda; Akimoto, Youhei (Optics express, 2022)
Various strategies have been proposed to achieve invisibility cloaking, but usually only one phenomenon is controlled by each device. Cloaking an object from two different waves, such as electromagnetic and acoustic waves, is a challenging problem, if not impossible, to be achieved using transformation theory and metamaterials, which are the major approaches in physics. Here, by developing topology optimization for controlling both electromagnetic and acoustic waves, we present a multidisciplinary attempt for designing biphysical cloaks with triple-wave cloaking capabilities , specifically for E z - and H z -polarized waves and acoustic wave. The topology-optimized biphysical cloak cancels the scattering of the three waves and reproduces the original propagating waves as if nothing is present, thus instilling the desired cloaking capability. In addition, we describe cloaking structures for multiple incident directions of the three waves and structures that work for both electromagnetic waves and sound waves of different wavelengths.